Pengaruh Gaya Kepemimpinan, Kompensasi, dan Pendidikan terhadap Kinerja Karyawan di STIKES Surya Global : Human Resource Development, Leadership, Compensation, Education, Employee Performance - Moh Sholihin (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This study aims to analyze the influence of leadership, compensation, and education on employee performance at Stikes Surya Global Yogyakarta, individually and collectively. The respondents in this study consist of directors, lecturers, and administrative staff at Stikes Surya Global Yogyakarta. The saturated sampling method was used to select the respondents. Primary data were collected through questionnaires, while secondary data were obtained from relevant sources. This study employs a quantitative approach with statistical data analysis techniques. The results indicate that leadership has a positive and significant impact on employee performance. Similarly, compensation and education also have positive and significant effects on employee performance. When examined simultaneously, leadership, compensation, and education collectively contribute to improving employee performance. Effective leadership fosters a conducive work environment, fair compensation enhances job satisfaction, and higher education improves employees' competence in performing their duties. This research provides both academic and practical contributions to the development of human resource management, particularly in enhancing the effectiveness of higher education institutions. By implementing the right strategies in leadership, compensation, and education, Stikes Surya Global Yogyakarta can continue to grow and improve its employees' performance sustainably.